Schaum's Fluid Mechanics and Hydraulics Problem 8-50: Oil Flow Between Two tanks - Adams, Thom (McGraw-Hill's AccessEngineering., 2013)
This video demonstrates how to calculate the required elevation difference between two tanks required to deliver a given flow rate of oil. The determination of head loss by calculating friction factor is illustrated.